2021
DOI: 10.3390/ijms22189916
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Chain Fatty Acid Butyrate Attenuates Pulmonary Vascular Remodeling and Inflammation in Hypoxia-Induced Pulmonary Hypertension

Abstract: Pulmonary hypertension (PH) is a progressive cardiovascular disorder in which local vascular inflammation leads to increased pulmonary vascular remodeling and ultimately to right heart failure. The HDAC inhibitor butyrate, a product of microbial fermentation, is protective in inflammatory intestinal diseases, but little is known regarding its effect on extraintestinal diseases, such as PH. In this study, we tested the hypothesis that butyrate is protective in a Sprague–Dawley (SD) rat model of hypoxic PH. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 98 publications
(132 reference statements)
0
17
0
1
Order By: Relevance
“…Liu et al found that GPR43 and GPR41 are expressed in human alveolar primary cells and regulated by intestinal-derived LPS, and directly verified the transmission of LPS and SCFA from the intestine to the lung using germ-free mice (Liu et al, 2021 ). It is reported that butyrate treatment can reverse the increase of CD68+ and CD163+ macrophages in the lungs of PAH rats induced by hypoxia (Karoor et al, 2021 ). Butyrate also exerts its anti-inflammatory effects by inhibiting the development of T helper 17 (Th17) cells and down-regulating VCAM-1 and CX3C chemokine Fractalkine in endothelial cells (Li et al, 2018 ; Chen et al, 2019 ; Karoor et al, 2021 ).…”
Section: Gut–lung Axis In Pahmentioning
confidence: 99%
See 3 more Smart Citations
“…Liu et al found that GPR43 and GPR41 are expressed in human alveolar primary cells and regulated by intestinal-derived LPS, and directly verified the transmission of LPS and SCFA from the intestine to the lung using germ-free mice (Liu et al, 2021 ). It is reported that butyrate treatment can reverse the increase of CD68+ and CD163+ macrophages in the lungs of PAH rats induced by hypoxia (Karoor et al, 2021 ). Butyrate also exerts its anti-inflammatory effects by inhibiting the development of T helper 17 (Th17) cells and down-regulating VCAM-1 and CX3C chemokine Fractalkine in endothelial cells (Li et al, 2018 ; Chen et al, 2019 ; Karoor et al, 2021 ).…”
Section: Gut–lung Axis In Pahmentioning
confidence: 99%
“…It is reported that butyrate treatment can reverse the increase of CD68+ and CD163+ macrophages in the lungs of PAH rats induced by hypoxia (Karoor et al, 2021 ). Butyrate also exerts its anti-inflammatory effects by inhibiting the development of T helper 17 (Th17) cells and down-regulating VCAM-1 and CX3C chemokine Fractalkine in endothelial cells (Li et al, 2018 ; Chen et al, 2019 ; Karoor et al, 2021 ). In addition to immune regulation, Karoor and Kim et al found that butyrate inhibited hypoxia-induced angiogenesis by decreasing the expression of VEGF-α and HIF-1α (Kim et al, 2007 ; Karoor et al, 2021 ).…”
Section: Gut–lung Axis In Pahmentioning
confidence: 99%
See 2 more Smart Citations
“…When the gut barrier is impaired, intestinal Gram-negative bacteria release lipopolysaccharides (LPS) into the bloodstream, causing Toll-like receptor 4 (TLR4)-mediated endotoxemia [ 18 , 19 ], which induces pulmonary perivascular inflammatory responses and thus promotes the development of PAH. Furthermore, variations in gut microbial metabolites facilitate perivascular inflammation and the proliferation of pulmonary vascular smooth muscle cells, thereby initiating lung injury and pulmonary vascular remodeling, and finally leading to PAH [ 20 , 21 , 22 ] ( Figure 1 ). However, the specific interaction between gut dysbiosis and PAH has not been clearly clarified.…”
Section: Introductionmentioning
confidence: 99%